2012
DOI: 10.1038/nm.3015
|View full text |Cite
|
Sign up to set email alerts
|

TRPM4 cation channel mediates axonal and neuronal degeneration in experimental autoimmune encephalomyelitis and multiple sclerosis

Abstract: In multiple sclerosis, an inflammatory disease of the central nervous system (CNS), axonal and neuronal loss are major causes for irreversible neurological disability. However, which molecules contribute to axonal and neuronal injury under inflammatory conditions remains largely unknown. Here we show that the transient receptor potential melastatin 4 (TRPM4) cation channel is crucial in this process. TRPM4 is expressed in mouse and human neuronal somata, but it is also expressed in axons in inflammatory CNS le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
192
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(202 citation statements)
references
References 57 publications
10
192
0
Order By: Relevance
“…As manganese poisoning progresses, catecholamine levels decrease, most likely due to the loss of nigrostriatal dopaminergic neurons, and consequently, parkinsonian-like symptoms ensue (37). Intriguingly, the pathological activation of TRPM4 in neurons has been shown to mediate axonal and neuronal degeneration (13). Therefore, the contribution of TRPM4 activation by Mn 2ϩ to the pathogenesis of manganism needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As manganese poisoning progresses, catecholamine levels decrease, most likely due to the loss of nigrostriatal dopaminergic neurons, and consequently, parkinsonian-like symptoms ensue (37). Intriguingly, the pathological activation of TRPM4 in neurons has been shown to mediate axonal and neuronal degeneration (13). Therefore, the contribution of TRPM4 activation by Mn 2ϩ to the pathogenesis of manganism needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, its mutations in the TRPM4 gene have been associated with cardiac conduction dysfunction in human patients (4, 10 -12). Furthermore, it has been shown that TRPM4 mediates axonal and neuronal degeneration in experimental autoimmune encephalomyelitis and multiple sclerosis (13).…”
mentioning
confidence: 99%
“…It inhibits sulfonylurea receptor 1 (SUR1, ABCC8), the regulatory subunit of the pancreatic potassium efflux channel (K ATP ) of the ATP-binding cassette (ABC) family. Recent reports have revealed that GLB may also have beneficial effects in acute ischemic, traumatic, and inflammatory central nervous system (CNS) injuries and diseases via its affinity for transient receptor potential melastatin 4 in the brain (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental autoimmune encephalomyelitis (EAE) was induced by immunization of female mice (12-14 wk) s.c. with 200 mg myelin oligodendrocyte glycoprotein peptide fragment 35-55 (NeoMPS, San Diego, CA) in CFA (BD Biosciences, Franklin Lakes, NJ) containing 4 mg/ml Mycobacterium tuberculosis (H37Ra; BD Biosciences), as described previously (26). We injected 200 ng pertussis toxin (Merck Millipore, Darmstadt, Germany) i.v.…”
Section: Animalsmentioning
confidence: 99%
“…on the day of immunization and 48 h later. Mice were scored for clinical signs by the following system: 0, no clinical deficits; 1, tail weakness; 2, hind limb paresis; 3, partial hind limb paralysis; 3.5, full hind limb paralysis; 4, full hind limb paralysis and forelimb paresis; and 5, premorbid or dead (26). Mice were analyzed at day 14 after EAE induction.…”
Section: Animalsmentioning
confidence: 99%